Illyefalvi Vitéz Géza jogászprofesszor, a Debreceni M. Kir. Tisza István Tudományegyetem 1926/27. tanévi rector magnificusa - Fónai, Mihály (Gerundium, 2016)
Géza Illyefalvi Vitéz Law Professor, the Rector Magnificus of István Tisza Hungarian Royal University in Debrecen During the Academic Year of 1926/27. Illyefalvi Vitéz Géza (1871–1931) studied at a university in Budapest, where he obtained a doctorate in law and political sciences. At the end of 1896 he was elected public ordinary professor of the judicial academy in Sárospatak, where he taught administrative law and statistics. He was a professor of the University of Debrecen after its establishment in 1914. In1921 he was appointed Dean of the Law Faculty and he was re-elected in 1931. Illyefalvi Vitéz Géza was Rector of the Hungarian Royal Tisza István University of Debrecen in 1926/27, the year when the clinic site was inaugurated, and the laying of the foundation stone of the main building took place. We can say that he was a rector at a destiny-shaping period of the University. He effectively represented the interests of the University, with the help of his contemporary higher education policy and the university development plans of Minister of Education Kunó Klebersberg. Illyefalvi wrote fourteen books and monographs, as well as numerous journal articles. These works are grouped in the two major fields of his interests, statistics and public finance. He also wrote university and judicial academy notes and textbooks.